2022
DOI: 10.1097/as9.0000000000000179
|View full text |Cite
|
Sign up to set email alerts
|

Coaching for Surgeons: A Scoping Review of the Quantitative Evidence

Abstract: Objective: To characterize quantitative studies on coaching interventions for professional surgeons to understand how surgical coaching is defined; examine how different coaching programs are designed, implemented, and evaluated; and identify any relevant research gaps. Background: Surgical coaching is gaining attention as an approach that could help surgeons optimize performance and improve overall wellbeing. However, surgical coaching programs and definitions of coaching … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…When considering elite athletes, coaching is one of the first performance-enhancing approaches that comes to mind. While mentoring often naturally occurs among surgeons, structured coaching is not routinely practiced . Surgical coaching differs from typical athletic coaching as it involves a nonhierarchical relationship between an individual surgeon and a trained coach, who can be a surgeon or a nonsurgeon professional.…”
Section: Coachingmentioning
confidence: 99%
See 4 more Smart Citations
“…When considering elite athletes, coaching is one of the first performance-enhancing approaches that comes to mind. While mentoring often naturally occurs among surgeons, structured coaching is not routinely practiced . Surgical coaching differs from typical athletic coaching as it involves a nonhierarchical relationship between an individual surgeon and a trained coach, who can be a surgeon or a nonsurgeon professional.…”
Section: Coachingmentioning
confidence: 99%
“…Recently, nonprofit organizations, such as The Academy for Surgical Coaching (https://surgicalcoaching.org), have promoted a theoretical framework for surgical coaching and provide specific training for coaches. Several well-structured peer-coaching programs implemented in North America have demonstrated that surgical coaching is well accepted and could have benefits for technical and nontechnical skills . In addition, coaching can help individuals achieve personal goals related to work-life balance and well-being.…”
Section: Coachingmentioning
confidence: 99%
See 3 more Smart Citations